IMPROVEMENT OF THE INTERNAL CONTROL SYSTEM OF ECONOMIC ENTITIES (Web of Teachers: Inderscience Research, 2025)
The article studies the experience of the country and foreign countries in this area, the development of scientific proposals and practical recommendations on the wide implementation of the country’s enterprise management system on the basis of international standards Actual problems related to organizational and economic fundamentals have been identified, and scientific proposals have been developed to solve them.